Gambaran Pengelolaan Obat di Puskesmas Oemasi Kabupaten Kupang - Jasmine Margareth Totos; Serlie K. A. Littik; Tanti Rahayu; Fransiskus G. Mado (Universitas Pahlawan Tuanku Tambusai, 2026)
Drug management is an important component in ensuring the quality of health services at public health centres. Non-optimal implementation can cause problems such as stock shortage, excess drugs, and expired drugs. Based on the initial data, there is still a discrepancy between the needs and availability of drugs as well as obstacles in the storage and distribution of drugs at the Oemasi Health Centre. This research aims to describe the implementation of drug management which includes planning, procurement, receipt, storage, distribution, control, and drug destruction. This type of research is descriptive with a qualitative approach. Informants are selected by purposive sampling which consists of 7 informants. Data collection is carried out through in-depth interviews, observations, and document studies. The data obtained is then processed through the stages of data reduction, data presentation, and drawing conclusions, as well as analysed qualitatively with a thematic approach to identify patterns and problems in drug management. The research results show that drug management has been running but not yet optimised. Planning and procurement refer to previous data, but there is still a mismatch of needs. Storage has not met the standard due to limited facilities. Distribution is still manual and evaluation is not routine. Stock control is not optimal so there is a difference between physical stock and record. Expired drugs are still found due to administrative constraints. It is concluded that the drug management at the Oemasi Health Centre is not fully in accordance with standards, especially in the aspects of storage, distribution, control, and destruction. It is necessary to improve the recording system, improve infrastructure, and strengthen supervision so that drug management can run more effectively and efficiently.